Scaling of computed tomography body composition to height: relevance of height‐normalized indices in patients with colorectal cancer. Issue 1 (6th November 2021) - Brown, Justin C.; Heymsfield, Steven B.; Caan, Bette J.
Abstract: Background: Body weight scales to height with a power of ≈2 (weight/height 2 ), forming the basis of body mass index (BMI). The corresponding scaling of body composition measured by abdominal computed tomography (CT) to height has not been established. The objective of this analysis was to quantify the scaling of body composition measured by a single‐slice axial abdominal CT image (skeletal muscle, and visceral, subcutaneous, and total adipose tissue) to height in patients with colorectal cancer (CRC). Methods: This cross‐sectional study included non‐Hispanic white males and females, aged 18–80 years, who were diagnosed with stage I–III CRC at an integrated health care system in North America between January 2006 and December 2011. Body composition was measured by a single‐slice axial CT image of the third lumbar vertebra and analysed with a semi‐automated threshold segmentation procedure. Allometric regression models were used to quantify height scaling powers ( β ± standard error) for each body composition measure, adjusted for age, for males and females. An interaction test was used to determine if height scaling powers were statistically significantly different between males and females. Results: Among 2036 subjects, the mean (standard deviation) age was 64 ± 11 years, 1008 (49.5%) were female, and the mean (standard deviation) BMI was 27.9 ± 5.4 kg/m 2 . Powers for skeletal muscle area were 1.06 ± 0.12 for males and 0.80 ± 0.12 for females ( P = 0.049). Powers for visceral adipose tissue area were 1.81 ± 0.64 for males and 0.57 ± 0.79 for females ( P = 0.16). Powers for subcutaneous adipose tissue area were 2.04 ± 0.42 for males and 0.81 ± 0.45 for females ( P = 0.056). Powers for total abdominal adipose tissue area were 1.80 ± 0.46 for males and 0.76 ± 0.50 for females ( P = 0.20). Conclusions: Body composition measured by single‐slice axial abdominal CT, particularly muscle area, scales to height with age‐adjusted powers that are different than 2 and are distinct between males and females. These observations may have implications for the development of height‐adjusted body composition indices in patients with cancer.